2010
DOI: 10.3329/jhpn.v28i2.4890
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Knowledge, Attitudes, and Practices of Women Living with HIV in Eastern Uganda

Abstract: HIV and AIDS have posed various medical, nutritional, social and economic problems, female-headed households being the most affected. Poor nutritional knowledge and dietary practices common among the most affected households significantly contribute to the rapid progression of HIV. However, very little data exist concerning these aspects of nutrition among women living with HIV and AIDS in resource-limited settings, such as Uganda. The aim of the study was to investigate the gaps in nutritional knowledge, atti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
30
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(39 citation statements)
references
References 14 publications
7
30
2
Order By: Relevance
“…The frequency at which the staples were consumed was higher than the other very important nutrients (from animal sources, fruits and vegetables) in the management of HIV. Another study in Eastern Uganda also showed a higher dependency HIV in Kayole Division, Nairobi-Kenya on starchy staples like maize, rice, sweet potatoes compared to foods of animal origin and fruits [20]. Interestingly there was a negative relationship between the nutrition knowledge and intake of oils and fats, and indicator of decrease of fats and oils intake with increase in nutritional knowledge.…”
Section: Discussionmentioning
confidence: 91%
“…The frequency at which the staples were consumed was higher than the other very important nutrients (from animal sources, fruits and vegetables) in the management of HIV. Another study in Eastern Uganda also showed a higher dependency HIV in Kayole Division, Nairobi-Kenya on starchy staples like maize, rice, sweet potatoes compared to foods of animal origin and fruits [20]. Interestingly there was a negative relationship between the nutrition knowledge and intake of oils and fats, and indicator of decrease of fats and oils intake with increase in nutritional knowledge.…”
Section: Discussionmentioning
confidence: 91%
“…The questionnaire also had provision for information on composition of household members by age, physiological status (for pregnant and lactating mothers), and gender. The constructs used to measure nutritional knowledge and attitude were adapted with modification from previous studies (Bukusuba, Kikafunda, & Whitehead, 2010;Damodaran, Parkin, & Fennema, 2008;Pilgrim et al, 2007). Literature study and laboratory analyses were undertaken to collect information on nutrient contents of the wild fruits and vegetables routinely consumed in the community.…”
Section: Study Population and Sampling Frameworkmentioning
confidence: 99%
“…8% respectively [16,17]. But this study nding is lower than the nding of Botswana Which was 30% [20] and higher than a study done in Dilla University Referral Hospital (12.3%) [18] and in Miami, Florida 17.6% [14]. The difference could be due to time difference.…”
mentioning
confidence: 69%